ANALISIS KONTRIBUSI PAJAK MOBIL TIPE LOW COST GREEN CAR (LCGC) TERHADAP PENERIMAAN PAJAK KENDARAAN BERMOTOR DI JAWA TIMUR TAHUN 2010-2014 - Sari, Nurul Kurnia; Hardi, Meiril (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTThis study aims to determine the magnitude of the contribution of the Low Cost Green Car type car tax to the tax revenue of Motorized Vehicles. Data Sources This study was obtained from interview and observation data (primary) and the target data and the realization of the East Java (Secondary) motorized vehicle tax. quantitative approach and descriptive data analysis method. The results of the analysis show that the contribution of the Low Cost Green Car car tax to the motor vehicle tax is still relatively small. In the second year its production increased by 200%. wagon jeep. Percentage of the level of effectiveness of motor vehicle tax from year to year has increased but has decreased in 2014. Keywords: Effectiveness, Contribution, Low cost green car, Motor vehicle tax, Local original income